My first 100 animals (London Priddy books, 2023)
With refreshed imagery and design, My First 100 Animals is an exciting new addition to the First 100 series. Your little one will learn some essential first words and pictures with this bright board book. There are 100 color photographs to look at and talk about, and 100 simple first words to read and learn, too. The pages are made from tough board for hours of fun reading, and now in new size that will be a great display on any child's bookshelf
Scientific Notions
Keywords: Science